Analisis Implementasi Otonomi Daerah dalam Bidang Pendidikan - Nursofah, Nursofah; Rugaiyah, Rugaiyah; Agus, Solikhin (Global Education Journal, 2023)
Educational autonomy is intended as the granting of several authorities in management education to the regions, without neglecting the authority of the Center and national standardization. The added value of educational autonomy can be seen from the independence of human resources in the regions in managing education, local people can feel the results of development education in the area in accordance with the needs and conditions of the region. that negative effect may be a minus value for the possible implementation of educational autonomy the occurrence of regional arrogance, which is caused by the striking differences between the various regions which exists. The purpose of this study is to analyze the implementation of regional autonomy in terms of education. This research method was carried out through a qualitative approach using library research methods with data sources referring to literature data. The results of the study show that the local government has implemented regional autonomy in the field of education in accordance with the mandate of the law, but in the field process there are still many obstacles that need to be corrected, irregularities in its realization are things that must be considered. be watched out for, so that the realization of community participation in developing the country through educational institutions also needs to be monitored and evaluated, to look for the advantages and disadvantages. In addition, the implementation of the regional autonomy policy still requires improvement to achieve the expected aims and objectives.